Will Demographic Changes Affect Monetary Policy with Interest Rate Shocks in Indonesia? - Ciplis Gema Qori'ah; Catur Sugiyanto; Amirullah Setya Hardi (Universitas Negeri Malang, 2022)
Changes in the demographic structure and its impact on the economy are becoming interesting issues in almost all countries in the world, including Indonesia. Until 2030, the working age group dominates almost 60 percent of the total population in Indonesia. This phenomenon is a valuable asset which should be used optimally. Moderate adjustment of interest rate policy is an effort applied by Bank Indonesia to maximize the access to credit and public savings. Therefore, this study aims to determine the effect of demographic aspects and the real sector on the effectiveness of monetary policy in the presence of interest rate shocks. This study employed time series data with a time period of 1987Q1 – 2020Q4 in Indonesia. The analysis was performed by using time varying parameter-vector autoregressive (TVP-VAR) and fully modified-ordinary least square (FM-OLS). The results revealed that the population and the elderly population aspects had significant positive effects on the monetary policy, while the variable of productive age and the number of dependence aspects has significant negative effects. The relationship between the real sector and the monetary policy has a different relationship, such as a positive relationship between the savings and technology variables and the domestic credit variable which has a significant negative relationship with the monetary policy.